Domain Ontology Evaluation in Software Development: Questionnaire Proposal - Lazaretti, Maria Gabriela Costa; Tenório Junior, Nelson Nunes; Teixeira, Thaise Moser (Anais da Escola Regional de Engenharia de Software (ERES); 2023: Anais da VII Escola Regional de Engenharia de SoftwareDO - 10.5753/eres.2023.237334, 2023)
Knowledge has become increasingly important as a resource for organizations. In line with this, there arises the need for the classification and organization of knowledge bases in knowledge-oriented organizations. In this regard, ontologies support the process of structuring and classifying information, facilitating and simplifying the continuous data processing. The present work aims to propose a questionnaire for the validation of a domain ontology.